Hemoglobin A2 Lowered by Iron Deficiency and α-Thalassemia: Should Screening Recommendation for β-Thalassemia Change?. (12th March 2013) - Denic, Srdjan; Agarwal, Mukesh M.; Al Dabbagh, Bayan; El Essa, Awad; Takala, Mohamed; Showqi, Saad; Yassin, Javed
Abstract : Screening for β -thalassemia trait (BTT) relies on measuring hemoglobin (Hb) A2 . Since multiple factors can affect HbA2 levels, the screening can become unreliable. In 1356 healthy Arabs enrolled into a federally funded premarital BTT screening program, the effects of iron deficiency (ID), α + -thalassemia trait, gender, smoking, and tribalism on HbA2 were studied. The complete blood count and hemoglobin fractions were determined on the entire cohort; serum ferritin (<15  μ g/L) in 391 subjects was used to determine ID. BTT was present in 29 (2.1%) subjects (HbA2 > 3.5%). Among 77(20.3%) subjects with ID, the mean HbA2 (2.30 ± 0.23 %) was 0.2% lower than in subjects without iron deficiency (2.50 ± 0.24 %, P < 0.0001 ). In 65 (38%)/172 subjects with phenotypic α + -thalassemia trait, the mean HbA2 (2.43 ± 0.24 %) was 0.13% lower than in subjects without α + -thalassemia trait, P < 0.0001 . The mean HbA2 did not differ between males and females, smokers and nonsmokers, and between the tribes. Thus, 35 (2.6%) subjects with HbA2 between 3.2 and 3.5% were at a risk of false negative diagnosis of BTT. Since iron deficiency and α + -thalassemia are both common and both lower HbA2, modifications in screening recommendations for BTT are proposed.